YEATS2 promotes malignant phenotypes of esophageal squamous cell carcinoma via H3K27ac activated-IL6ST - Zhai, Yuanfang; Zhang, Fanyu; Shi, Xiaoyu; Zou, Siwei; Hu, Xiaoling; Shan, Chengyuan; Zhang, Ling; Zou, Binbin; Yang, Xin; Kong, Pengzhou; Cheng, Xiaolong (Frontiers in Cell and Developmental Biology, 2025)
IntroductionHistone acetylation modifications can regulate gene transcription and play crucial roles in multiple tumorigeneses processes. YEATS domain proteins are one important type of acetylation readers. We have found significant mutations and copy number amplifications of YEATS domain containing 2 (YEATS2) gene in esophageal squamous cell carcinoma (ESCC) through whole genome sequencing (WGS). However, the function and molecular mechanism of YEATS2 in ESCC remain elusive.MethodsChi-squared test and Kaplan-Meier methods were used to analyze the clinical significance of YEATS2. MTT, Colony Formation Assay, Transwell, Scratch Wound Healing, subcutaneous tumorigenesis model and lung metastatic tumor model were performed to detect YEATS2 effect on the proliferation and migration ability of ESCC cells in vivo and in vitro Co-IP-based mass spectrum (MS) assays and Chromatin immunoprecipitation (ChIP) were performed to explore the molecular mechanism of YEATS2 function in ESCC.ResultsESCC patients with copy number amplification of YEATS2 had shorter postoperative survival. Furthermore, YEATS2 expression was positively correlated with copy number amplification. We have also found that YEATS2 expression was significantly upregulated in ESCC tissues and was correlated closely with the differentiation degree of ESCC cells. The results of in vivo and in vitro experiments revealed that YEATS2 enhanced the abilities of ESCC cells to proliferate and migrate. Mechanistically, YEATS2 activated NF-κB signaling to promote ESCC progression. YEATS2 and H3K27 acetylation (H3K27ac) were both enriched in the promoter region of IL6ST, which is involved in the regulation of YEATS2 on NF-κB signaling. Additionally, YEATS2 could recruit TAF15 and KAT5 to enhance H3K27ac enrichment in the promoter region of IL6ST to regulate its expression.ConclusionIn conclusion, YEATS2 might function as a potential driver gene and a potential therapeutic target in ESCC.